Design and Simulation of a Versatile Electric Cooking Stove. - Mukama, Percy Murungi (Kabale University, 2024)
The “Design and Simulation of a Versatile Electric Cooking Stove” project, conducted in Uganda, aimed to develop a versatile, efficient, and cost-effective electric stove. The project’s objectives included the determination of the design specifications of the stove, the development of the stove’s layout, and the evaluation of the stove’s performance by simulation. The research methodology incorporated a qualitative approach, utilizing interviews, observations, and desk research. The findings revealed the popularity of charcoal stoves, stressing the need for a versatile stove capable of repetitive use, and the trade-off between speed and cost for different stove types. The simulation results, particularly those related to structural integrity and thermal performance, guided the design refinement process. The study successfully designed key elements such as the supporting frame for stability, strength, and insulation of the internal chamber and appliance body, and simulated and analyzed the motion mechanisms relevant for adjusting heater positioning. Despite the absence of a prototype and other challenges, the project made significant strides in its development period.